Academic self-concept as the predictor of secondary school adolescent students’ school engagement - Ejigu Olana; Belay Tefera (Institute of Advanced Engineering and Science, 2022)
The objective of this study was to examine the role of academic self-concept (ASC) in predicting adolescent students’ school engagement by using a cross-sectional research design. Data was collected from 278 (149 males and 129 females) Ethiopian adolescents aged 15 to 20 years old. The result of regression analysis indicated that socioeconomic status (SES) and ASC significantly contributed to the overall school engagement score and the four components of school engagement (behavioral, emotional, cognitive, and agentic engagement). Additionally, the results from hierarchical regression revealed that SES significantly moderated the relationship between ASC and school engagement (β3=1.323; ∆R2=.033, p<.01). However, gender and grade level did not significantly relate to school engagement. As conclusion, ASC is a significant personal trait that has been linked to school engagement in which students from high SES are more advantageous regardless of their gender and grade levels.